Empirical study of burnout in socionomy specialists through positive psychotherapy - Melnychuk Antonina Yuriivna; Komar Taisiia Vasylivna; Onyshchuk Tetiana Petrivna (Insight: the psychological dimensions of society, 2023)
The article presents an empirical study of burnout using positive psychotherapy by N. Peseschkian, which aims to cover and analyze burnout in the specialists of socionomic professions through the prism of positive psychotherapy. Methods. The study was conducted using two inventories: the Wiesbaden Inventory for Positive Psychotherapy and Family Psychotherapy (WIPPF) and Burnout Inventory (K. Maslach and S. Jackson adapted by N. Vodopianova). 134 socionomy specialists took part in the empirical study. Results. Positive psychotherapy is an integrative method with a large toolkit for analyzing and improving the quality of life, including the balance model, actual abilities, the model dimension, etc. Spearman’s correlation analysis (r) assisted in establishing that specialists with a high level of emotional exhaustion have the most developed actual abilities: accuracy, tidiness, politeness, diligence, achievement, justice, patience, and faith. Moreover, the higher the emotional exhaustion is, the lower the actual ability – hope – is. In other words, a specialist loses hope for the best due to overwork and exhaustion. The high level of reduced personal achievements comes amid the mean actual ability of “diligence-achievement”, upon which an individual loses the desire to work and grow professionally. Conclusions. An imbalance in the distribution of vital energy can cause burnout progress. It is generalized that excessive attention to a career can lead to emotional exhaustion and individual depersonalization. A high level of emotional exhaustion is followed by a low level of the “contacts” area. A specialist paying attention and all their energy only to work and forgetting about other areas, including contacts, is more prone to burnout. Thus, positive psychotherapy means are effective for analyzing the causes and growth dynamics of burnout in socionomy specialists. In addition, these tools can be advantageous for preventing and correcting the relevant phenomenon.